Comparison of Different Methods on Post-Activation Performance Enhancement: A Meta-Analysis - Zhao, Chunyu; Li, Congying; Su, Ronghai; Chen, Lin; Wei, Wei; Meng, Meng; Chen, Chen (International Journal of Sports Medicine, 2025)
This meta-analysis was aimed to compare the effects of two methods on post-activation performance enhancement (PAPE). We conducted a comprehensive search of PubMed, Web of Science, Cochrane Library, and China National Knowledge Infrastructure from inception to December 2023. Two authors independently selected the included studies, extracted data, and assessed the risk of bias and certainty evidence. The primary meta-analysis compared the effects of blood flow restriction combined with resistance training (BFR-RT) and high-load resistance training (HL-RT) on the indicator jump height (JH) and power output (PO) of PAPE. The secondary meta-analyses compared within-group differences by gender and between-group differences between the optimal combined protocol of arterial occlusion pressure (AOP) combined with resistance load and the HL-RT protocol. This meta-analysis shows that both BFR-RT and HL-RT significantly improved JH (standardized mean difference (SMD)=0.39, 95% confidence interval (CI) [0.20, 0.59]) (SMD=0.34, 95% CI [0.19, 0.48]) and PO (SMD=0.42, 95% CI [0.21, 0.62]) (SMD=0.37, 95%CI [0.19, 0.54]), and there was no significant difference between them. However, subgroup analysis revealed that in terms of gender, BFR-RT was more beneficial for PAPE in females, and in terms of combined protocol, BFR-RT with 50% AOP+30% 1 repetition maximum had the greatest effect compared to HL-RT.BFR-RT can serve as an effective alternative to HL-RT for inducing PAPE.
Keywords: warm-up activities; sports performance; explosive power; induction methods